Islamic Philanthropic Institutions in the Development of Education and Economic Empowerment - Nur Diana Dewi; Ahmad Zaenurrosyid (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2023)
The challenges faced by the nation in the current era are increasingly diverse, both in the fields of education and the economy. The basic needs needed for the development of both the economic and educational sectors rest on adequate financial support, as well as a strong mentality from the actors involved. This research aims to present an analysis of empowerment programs in the fields of education and the economy carried out by Islamic philanthropic institutions. The method used in this discussion is a qualitative approach, with data sources from informants involved in fundraising programs for Islamic philanthropic institutions, Daarul Quran in particular. Some of the findings of this study are first, Daarul Quran institutional empowerment program focuses on developing productive economic activities for the community, consolidating education to prepare the generation of the Qur’an, and then prioritizing religious values ​​and moral culture for every individual in society. Second, effective management of philanthropic institutions is achieved through professional and integrated management. Third, As philanthropic institutions, some of them face challenges in community empowerment, especially in the economic and educational fields which are heavily influenced by public trust. Then, well-managed philanthropic institutions support for the development of the education sector and the community's economy.